MESIN PENCACAH SAMPAH ORGANIK TIPE PIRINGAN DENGAN KEMIRINGAN SUDUT HOPPER INPUT 60 DERAJAT - Saparin Saparin; eka Sari Wijianti; budi santoso wibowo (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2022)
ABSTRACT Waste can be divided into two categories: organic waste and inorganic waste. Compost produced from organic waste has the potential to be created. The purpose of this research is to create a crusher for organic waste. The engine's designed specifications called for such a 6.5 HP gasoline engine with a pulley and belt transmission. 1918 mm in length, 639 mm in width, and 1046 mm in height compose up the entire engine. The blade's dimensions are 160 mm in length, 60 mm in width, and 10 mm in thickness. The blade's cutting angle is inclined at a 30 °. There are two pieces of chopping blades. The rotor blade shaft rotates around 1694 to 1741 rotations per minute. The test mass is 2900 grams, and the test duration is 32.10 seconds. The input hopper angle is 60 degrees slant. The machine does have a production capacity of 293.93 kg per hour. The machine's production efficiency is 92.82%. Keywords: crusher, waste processing